2020
DOI: 10.18280/ijht.380112
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transportation in Copper Oxide-Water Nanofluid Filled Triangular Cavities

Abstract: This paper performs a comparative analysis of two-dimensional transient water-copper oxide nanofluid flow and heat transportation inside a right-, acute-and obtuse-angled triangular cavity in the presence of a magnetic field. The vertical and inclined walls of the enclosure are maintained at a constant low temperature whereas the base wall is heated by a uniform thermal condition. The finite element method is used to solve the principal equations of nanofluid within the cavities along with the wall conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…nf of are available in the works of Uddin 25 , and Uddin and Rahman. 26 As the domain of the study is 3D, the heated bottom surface is the function of xy space. In the present study, the temperature of the bottom surface is assumed as parallel to the x-axis and perpendicular to the z-axis.…”
Section: Modelmentioning
confidence: 99%
“…nf of are available in the works of Uddin 25 , and Uddin and Rahman. 26 As the domain of the study is 3D, the heated bottom surface is the function of xy space. In the present study, the temperature of the bottom surface is assumed as parallel to the x-axis and perpendicular to the z-axis.…”
Section: Modelmentioning
confidence: 99%
“…The chamber turning effect has a bigger influence on the Nusselt number's value when low Rayleigh numbers were used. The three different types of nanoparticles that the researchers studied were Ag, CuO, and Al2O3 nanoparticles in the rectangular enclosure using two heat sources positioned at the depression's centre and base wall with a focus on free convection is studied by [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the size of the particles enhances the temperature flow rate. Uddin and Rahman [44] also performed the heat transportation of nanofluids within triangular cavities. Qayyum et al [45] studied a comparison study of viscous liquid including Joule heating for various nano-sized particles.…”
Section: Introductionmentioning
confidence: 99%